MACROSCOPIC IDENTIFICATION OF CRUDE DRUGS FOR AYURVEDIC FORMULATIONS - Kumar Sanger, *Rupesh; Singh, D.C.; Chaubey, Suresh; Kumar, Naveen (International Journal of Ayurveda and Pharma Research, 2016)
There are certain diseases in which western medicines are still lacking cure. It is important to note that western medicine is undoubtedly effective for symptomatic control of these disorders but still lacking cure for potential. Apart from this these drugs are having numerous side effects. Keeping this fact in mind the attention diverts towards our ancient system of medicine i.e Ayurveda for radical cure of these diseases. The demand for plant derived products is increasing day by day. For preparation of any Ayurvedic formulation proper identification of crude drug is extremely necessary. Identification of crude drug involves the morphological or macroscopic details and microscopic parameters. These parameters are necessary for the preparation of accurate and potent formulations. Identification of crude drug is the most important step in development of standards for herbal drugs a lot of adulteration is being done. The major problems affecting the quality of crude drug are adulteration or substitution, degradation due to faulty collections, drying or storage. A well known example is of drug Ashoka which is the stem bark of Saraca indica, the material available in the market is frequently found to be Polyalthia longifolia.